The Profile of the Brazilian Cardiologist - A Sample of Members of the Brazilian Society of Cardiology - Lucas Simonetto Faganello; Mauricio Pimentel; Carisi Anne Polanczyk; Tiago Zimerman; Marcus Vinicius Bolivar Malachias; Oscar Pereira Dutra; Leandro Ioschpe Zimerman (Arquivos Brasileiros de Cardiologia)
Abstract Background: Data from the international literature have shown changes in the profile of cardiologists and in their medical practices. However, there is no data on this in Brazilian cardiologists. Objective: To evaluate professional and personal characteristics of a sample of Brazilian cardiologists. Methods: This was a cross-sectional study; a questionnaire was sent by e-mail to cardiologists, active members of the Brazilian Society of Cardiology in 2017. The results were analyzed, and the level of significance set at p < 0.05. Results: The questionnaire was sent to 13,462 cardiologists, with 2,101 (15.6%) respondents, mostly men (71.8% versus 28.2%). Age distribution and marital status were significantly different between the sexes (p < 0.001). The number of cardiologists without children was higher among women (40.5% versus 16.1%; p < 0.001). The most common place of work was the public hospital (46.5%), followed by private hospital (28.5%) and private office (21.1%). The office was the main place of work for 23.9% of men and 14% of women (p < 0.001), with predominance of individuals older than 50 years (31.7% versus 10.1%, respectively; p < 0.001). Most cardiologists (64.2%) worked more than 40 hours a week (69% of them men and 51.9% of the women; p < 0.001). Eighty-eight percent of the sample earned more than BRL 11,000 (US$ 3,473.43), and 66.5% of the men earned more than BRL 20,000 (US$ 6,315.32) per month, versus 31.2% of the women (p < 0.001). A high level of work-related stress was reported by 11.3% of respondents. Conclusion: Most cardiologists were men, who showed higher workload and higher income; 11.3% of the cardiologists perceived stress as a great deal.